Investigation of the Effect of Polymer Emulsion on the Uniaxial Compressive Strength of Aeolian Sand - Mahsa Heravi; Akbar Cheshmi (پژوهش‌های زیرساخت‌های عمرانی, 2023)
The present study investigated the effect of vinyl acrylic polymer emulsion (VA) on maximum dry density (γdmax), optimum water content (ωopt), uniaxial compressive strength (UCS) and modulus of elasticity (E) of aeolian sands of Khuzestan plain. Polymer emulsion with percentages of 10, 20, and 30% were made and after adding to the soil, they were subjected to a compaction test, then cylindrical samples with γdmax and ωopt were made and at curing times 1, 7, 14, 21 and 28 days in two groups were subjected to UCS test. The samples of the first group were cured at laboratory temperature and the samples of the second group were packed with nylon in order to maintain moisture and were cured at a temperature of 20 C. The results of the tests showed that increasing the concentration of the polymer solution had no effect on the γdmax, but it could reduce ωopt. By increasing the curing time and the concentration of the polymer solution, the UCS and E of the first group of samples increased, while the UCS of the second group is without change. Therefore, when the improved sample is tested in a dry state, the UCS increases, and when it is tested in a wet state, the UCS does not change. The electron microscope images show that when the sample is dry the polymer forms bonds and bridges between the sand grains and the UCS and E increase.